To Compare the Effect of Intravitreal Bevacizumab on the Resolution of Macular Edema Secondary to Diabetic Retinopathy and Branch Retinal Vein Occlusion - Zeeshan Kamil, Fawad Rizvi, Syeda Aisha Bokhari (Pakistan Journal of Ophthalmology, 2012)
Purpose: To assess the efficacy of intravitreal bevacizumab in treating patients with macular edema secondary to diabetic retinopathy and retinal vein occlusion. Material and Methods: This comparative study was carried out in LRBT Free Base Eye Hospital, Karachi from 1st March 2010 to 28th February 2011. Total 60 patients were recruited for the study among which 32 (53.33%) were male and 28 (46.66%) were female, with age ranging from 40-65 years. Out of the 60 patients, 35 (58.33%) were diagnosed with macular edema secondary to diabetic retinopathy, and 25 (41.66%) with macular edema secondary to branch retinal vein occlusion. They were classified into Group A and Group B respectively. Informed written consent was obtained from all the patients before their participation in the study. Detailed medical and ophthalmic history was recorded. Baseline assessment of patients included best-corrected visual acuity (BCVA) on snellen chart, slit lamp examination of anterior segment and posterior segment (using 78D/90D lens), indirect fundoscopy with 20D lens, intraocular pressure measurement, colour fundus photography, fundus fluoresein angiography and optical coherence tomography. All the patients were treated with 2 injections of intravitreal bevacizumab 1.25 mg/0.05 ml, at an interval of 6 weeks, and assessment was carried out at 6 weeks and 12 weeks. Efficacy of intravitreal bevacizumab was assessed in terms of improvement in BCVA and reduction of macular thickness. Results: 60 patients were enrolled in this study and were followed for a period of 3 months. Group A: at the end of three months, 27 (77.14%) out of 35 patients showed improvement in BCVA of 2 snellen lines from baseline, and the mean central macular thickness (CMT) reduced from 502?m to 384?m. Group B: At the end of three months, 17 (68%) out of 25 patients showed improvement of BCVA of up to 2 snellen lines and mean CMT reduced from 510?m to 370?m. No serious adverse effects were observed in both the groups such as inflammation, increased intraocular pressure, endophthalmitis or thromboembolic event. Conclusion: Intravitreal bevacizumab injection for macular edema caused by branch retinal vein occlusion and diabetic macular edema was safe and effective for improving visual acuity and reducing central retinal thickness.